TOXICITY AND TREATMENT OUTCOME OF ACCELERATED FRACTIONATION RADIOTHERAPY VERSUS CONVENTIONAL FRACTIONATED CONCOMITANT CHEMORADIATION IN LOCALLY ADVANCED CERVICAL CARCINOMA: A PROSPECTIVE STUDY - DARIPA, SHARMISTHA; BANERJEE, SAPTARSHI; SADHYA, APARAJITA; BERA, ANJAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The benefit of concurrent chemoradiation is often not achievable due to poor tolerance due to increased toxicity, which is a common problem in our setting, where a significant portion of carcinoma cervix patients presents at an elderly age, with medical comorbidities, and with poor performance status. In addition, many patients refuse chemotherapy. Accelerated radiation therapy remains one of the possible alternatives there. Hence, we would like to perform a prospective study to compare treatment results between Pure Accelerated Radiation versus Concomitant Chemoradiation in Locally Advanced Squamous Cell Carcinoma of Cervix. Methods: After the initial investigative work, a total of 62 histologically confirmed squamous cell carcinoma of cervix locally advanced stage (FIGO-stage IB2 to IVA.) with ECOG performance status 0–2 patients were randomized into two arms: Arm A (Study arm, n=30) – Patients received Six fractions per week of External Beam Radiotherapy without chemotherapy and Arm B (Control arm, n=32) patients received concurrent chemoradiation with Five fractions per week of radiation with Weekly Injection of Cisplatin at the dose of 40 mg/m2. Results: Overall response rates between the two arms were similar and statistically not significant (p=0.352). All acute late toxicities are similar in both arms except acute renal toxicity which is more in the control arm and the difference is statistically significant (p=0.005). Conclusions: In developing countries like India with limited treatment facilities, pure accelerated RT with brachytherapy, without concurrent chemotherapy, may be a good option and it can be viewed as an equally effective option for the elderly patients, the patients who refuse, those who have contraindications for chemotherapy, or have comorbidities. Further, multicenter, controlled, and Phase III trials will be needed to prove the benefit of the shortening overall treatment time and compare the efficacy with chemoradiation.